Stylized statistical properties in bloc-based financial markets - Samuel K.-B. Dzidzornu; Sonia D. Tamakloe (Research in Statistics)
Empirical stylized properties have been widely theorized since the emergence of seminal research on financial market dynamics. Across decades, financial markets have evolved in data complexity and interrelational sophistication at far-reaching scales. As such, the relevance of stylized properties in contemporary markets remains a pertinent field of inquiry in financial statistics. The study explores the persistence of stylized properties and regime shift dynamics in the equity returns of three BRICS economies—Brazil, China, and India—over a 13-year period. Five integral stylized facts are examined: non-Gaussianity of returns, aggregational Gaussianity, volatility clustering, gain/loss asymmetry, and slow autocorrelational decay of absolute returns. Computational methods employed in the investigation substantiate four of the phenomena, with slow autocorrelational decay remaining uncorroborated. Further, a comprehensive regime shift analysis, utilizing the Pruned Exact Linear Time (PELT) algorithm and Hamiltonian Markov Switching Autoregressive (MS-AR) models, is performed to assess four thematic dynamics: distributional change points, regimes and transitional characterizations, filtered state probabilities, and expected regime durations. The findings suggest that the Brazilian and Chinese markets exhibit elevated risk profiles relative to the Indian market, with Brazil characterized by higher risk than China. The study contributes empirical insights to advance theoretical discourse and inform market applications.